Schwingungseigenschaften des ReF₆⁺-Ions - Baran, Enrique José (1976)
The principal force constants for ReF₆⁺ have been calculated using the GVFF. Mean amplitudes of vibration and bond orders are also estimated. The results are briefly discussed and some comparisons with related species are made.